Japan’s International Standards of Waste Recycling Treatment: Disseminating the Osaki System in Depok and Bali - Purnamawati Purnamawati (UNHI PRESS, 2021)
This research explains the importance of approach and coordination from the Osaki Town government on waste recycling management of Osaki System to the community residents and companies, for changing their mindset on responsibilities and duties. This was done since the beginning when Osaki system was created until it becomes a sustainable system in daily life. The important key aspects on implementing the Osaki system are good cooperation and bond of trust shared among the government, community residents and companies. Osaki Town has achieved no.1 in the highest rate of waste resource recycling for 12 consecutive years in all of Japan. The system has made Osaki Town to become a SDGs system model in Japan, after receiving SDGs award from the Japanese government in December 2019. The Osaki System has succeeded to solve problems on reducing the volume of waste in landfill site. Being a sustainable waste resource recycling system and a model not only in Japan but also abroad, Osaki Town then disseminates the Osaki System in Indonesia which has the same problems, such as approach and cooperation between the government and the residents, reduce the waste volume in landfill areas by separate waste method for recycling and low cost management.